51‐2: Pixel Design Solutions for Transmittance Improvement in 8k VA LCD. Issue 1 (29th May 2019) - Zhang, Yinfeng; Li, Xuan; Zhang, Yihe; Cao, Wu; Zhang, Qi; Lin, Yunglun; He, Jhenwei; Chiu, Chung-yi; Lin, Ray; Zhang, Min
Abstract : The transmittance loss with development of UD and low frame rate to 8k and high frame rate in high‐specification display has been an increasing urgency. Attempts have been made through domain reduction design to improve the transmittance and positive feedback has been received in the 65 inch and 75 inch 8k VA LCDs. Some variable domain designs are furthermore demonstrated to be impressively effective to modify the dark fringe and contribute to the transmittance improvement. A representative display sample adopting domain reduction design is displayed.